Implementation of Outdoor Learning Methods in Improving The Motivation of Mts Al-Mu'in Students in Tangerang City to Learn Fikih - Azka Azmil Arifin; Dede Ibrahim; Awaludin Adnan (Edukasiana: Journal of Islamic Education, 2026)
This study was motivated by the low learning motivation of students in fiqh lessons, which have been dominated by the use of conventional lecture methods. This condition causes students to tend to be passive and easily bored in the learning process. Based on these issues, this study focuses on answering the following questions: (A) How is the outdoor learning method implemented in the teaching of fiqh to seventh-grade students at MTs Al-Mu'in in Tangerang City, and (B) How is the implementation of the outdoor learning method in the teaching of fiqh to seventh-grade students at MTs Al-Mu'in in Tangerang City evaluated? The purpose of this study is to determine the application of the outdoor learning method in an effort to increase motivation to learn fiqh and to analyse the extent to which this method can increase student motivation to learn. This study uses a qualitative approach with a case study method, with the research subjects including fiqh teachers and seventh grade students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which included the stages of data reduction, data presentation, and conclusion drawing and verification. The results showed that the application of the outdoor learning method was effective in increasing students' motivation to learn fiqh. Through learning activities outside the classroom, such as practising worship in the mosque and observing the school environment, students became more active, enthusiastic, and had a better understanding of fiqh material. In addition, teachers also showed increased creativity in designing more contextual and interesting lessons. Thus, it can be concluded that the outdoor learning method has a positive impact on increasing student learning motivation and supports the achievement of fiqh learning objectives optimally.